Nekateri vidiki timskega dela v vrtcu - Lepičnik-Vodopivec, Jurka (Sodobna pedagogika, 2006)
The article addresses team planning and the implementation of pre-school education in a kindergarten unit from the point of view of the teachers and their assistants. It presents the applicable professional basis for the operation of teams in kindergartens and the roles played in the teams. It summarises the opinions of kindergarten teachers and their assistants about team planning and the implementation of pre-school education at the level of a kindergarten unit, and their assessments of the roles experienced in the team at the unit level.
Keywords: predšolska vzgoja; otroški vrtci; vzgojitelji; predšolski otroci; timsko delo